The Impact of the Implementation of Brain-Based Learning Strategies to Enhance Intensive Basic English Students' Group 4 Oral Production at the Western Multidisciplinary Campus of the University of El Salvador, Semester I, 2020 - Chanico Escalante, Juan Enrique; Cruz García, Brenda Gabriela; López De Deras, Gisela Abigail; Mata Godínez, José Astul; Ramírez Chinchilla, William Antonio (2024)
The present Holistic Projective Research is focused on “The impact of the Implementation of Brain-Based Learning Strategies to enhance Intensive Basic English Students’ Group 4 Oral Production at the Western Multidisciplinary Campus of the University of El Salvador, Semester 1, 2020”. Altogether, researchers’ main purpose on this study is to accomplish the general objective which is to demonstrate the effectiveness of the “Brain-based learning Strategies” to help teachers better students’ oral production during semester I, 2020 at the Western Multidisciplinary Campus of the University of El Salvador.